Meteorological Data Measured at Biological Hut, the Yukidori Valley, Langhovde, Antarctica in the Austral Summer of 1987-1988 and 1988-1989 - OHTANI, Shuji; KANDA, Hiroshi; OHYAMA, Yoshikuni; MOCHIDA, Yukira; SUGAWARA, Hiromi; INO, Yoshio (National Institute of Polar Research, 1992)
P(論文) departmental bulletin paper